The Influence of Online Media Marketing Communication Among Youth in Medan City - Khairifa, Feni; Mardhiyah, Ainun (Research Horizon, 2023)
As social beings, communication plays a crucial role in human life. Communication activities naturally occur when humans interact with one another, demonstrating that communication is an inherent outcome of social relations. This definition underscores that communication is inseparable from human existence, whether at an individual or group level. This research aims to investigate the influence of social media and e-commerce on online marketing communication among youth in Medan City. This study explores the impact of online platforms on adolescent online commerce communication. It uses a mixed-methods approach, combining interviews and Focus Group Discussions (FGD) with quantitative data collected through questionnaires. The findings show that online media, including social media and e-commerce, significantly influence how adolescents in Medan city communicate when buying and selling online.